Do E-Commerce and E-Wallets Matter for Increasing Marginalized Entrepreneurs’ Income? - Maulida, Sri; Almadina, Agatha (International Journal of Zakat, 2023)
This study investigates the impact of utilizing e-commerce and e-wallets on the income enhancement of mustahik entrepreneurs assisted by BAZNAS in South Kalimantan Province. In particular, this research tests the degree to which the use of e-commerce and e-wallets impacts those marginalized entrepreneurs’ income improvement. Multiple linear regression models and classical assumption tests are used to evaluate the data gained from the close-ended questionnaire, distributed to the sample of 35 mustahiks in South Kalimantan Province, who are small entrepreneurs supported by BAZNAS. The results show that e-commerce and e-wallets significantly increase the sample’s income. Practical and theoretical implications are drawn from the findings.